KEDUDUKAN HARTA PERKAWINAN SETELAH PERCERAIAN DITINJAU DARI KOMPILASI HUKUM ISLAM - Iskandar Laka (Res Judicata, 2019)
The definition of property in marriage according to Law Number 1 of 1974 concerning marriage is abbreviated (Law No. 1 Year 1974) in Article 35 states that the property obtained in marriage becomes a joint asset, while the subordinate assets of each husband or wife and property acquired by each husband or wife as a gift or inheritance under their respective supervision insofar as the parties do not determine otherwise. According to Article 37 of Law Number 1 Year 1974 concerning abbreviated marriage (Law No. 1 Year 1974), it is explained that: "If marriage breaks out due to divorce, joint assets are regulated according to their respective laws, while for legal matters this marriage property often gets less attention in a marriage. The law of marital property has only recently received attention after a dispute between husband and wife who have broken up in marriage, so that in order to solve the problem of the marriage property an institution which is in it is needed to solve the problem, namely the Religious Court.